2009
DOI: 10.1007/s10803-009-0707-6
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Biochemical Correlates of Clinical Impairment in High Functioning Autism and Asperger’s Disorder

Abstract: Amygdala dysfunction has been proposed as a critical contributor to social impairment in autism spectrum disorders (ASD). The current study investigated biochemical abnormalities in the amygdala in 20 high functioning adults with autistic disorder or Asperger’s disorder and 19 typically developing adults matched on age and IQ. Magnetic resonance spectroscopy was used to measure n-acetyl aspartate (NAA), creatine/phosphocreatine (Cre), choline/choline containing compounds (Cho), and Myoinositol (mI) in the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…Although the majority of MRS studies have reported lower NAA in at least one studied region in autism (Chugani, Sundram, Behen, Lee, & Moore, 1999; DeVito, et al, 2007; Endo et al, 2007; Friedman et al, 2006; Gabis et al, 2008; Hardan, et al, 2008; Hisaoka, Harada, Nishitani, & Mori, 2001; Levitt et al, 2003; Otsuka, et al, 1999), this is not a universal finding among regions even within the same study. To our knowledge, higher NAA has been reported in only one prior study (Murphy et al, 2002), although other studies do not find NAA differences between ASD and comparison groups (Bernardi, et al, 2011; Harada, et al, 2010; Kleinhans et al, 2009; Page, et al, 2006; Vasconcelos et al, 2008; Zeegers, van der Grond, van Daalen, Buitelaar, & van Engeland, 2007). Ages of participants are widely variable among the published studies, but could also potentially contribute to the mixed findings for NAA, as NAA (NAA/Cr and NAA/Cho) is reported to increase dramatically from 1 month to 3 years, with changes observed until 16 years (van der Knaap et al, 1990).…”
Section: Discussioncontrasting
confidence: 63%
“…Although the majority of MRS studies have reported lower NAA in at least one studied region in autism (Chugani, Sundram, Behen, Lee, & Moore, 1999; DeVito, et al, 2007; Endo et al, 2007; Friedman et al, 2006; Gabis et al, 2008; Hardan, et al, 2008; Hisaoka, Harada, Nishitani, & Mori, 2001; Levitt et al, 2003; Otsuka, et al, 1999), this is not a universal finding among regions even within the same study. To our knowledge, higher NAA has been reported in only one prior study (Murphy et al, 2002), although other studies do not find NAA differences between ASD and comparison groups (Bernardi, et al, 2011; Harada, et al, 2010; Kleinhans et al, 2009; Page, et al, 2006; Vasconcelos et al, 2008; Zeegers, van der Grond, van Daalen, Buitelaar, & van Engeland, 2007). Ages of participants are widely variable among the published studies, but could also potentially contribute to the mixed findings for NAA, as NAA (NAA/Cr and NAA/Cho) is reported to increase dramatically from 1 month to 3 years, with changes observed until 16 years (van der Knaap et al, 1990).…”
Section: Discussioncontrasting
confidence: 63%
“…Neuroimaging of metabolic activity in regions implicated in ASD was able to distinguish ASD cases with and without language impairment [Gabis et al, 2008]. Recently, Kleinhans et al [2009] showed positive correlation of IQ and neurometabolites in the amygdala region of high‐functioning ASD patients. As this work is preliminary, there are presently no laboratory tests specific to the ASP diagnosis or that differentiate clinical subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the results from these different studies is impeded for a number of reasons. Some authors examined the amygdala of children, where at least lower tNAA and higher tCho than in adults may be expected . Furthermore, none of the previously reported results has been obtained with a measured MM baseline.…”
Section: Discussionmentioning
confidence: 97%